Optimlisasi Jumlah Tanaman per Lubang Tanam terhadap Pertumbuhan dan Produksi Tanaman Bayam Batik dengan Hidroponik Sistem Rakit Apung - Putri, Dirgahani (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
The large population has an impact on competition between plants in the use of nutrients, sunlight and water. Setting the right number of plants per planting hole will reduce competition between plants in terms of receiving sunlight, nutrient absorption and water. This study aims to determine the optimization of the number of plants per planting hole and to find the optimal weight on the growth and production of batik spinach plants with hydroponic floating raft system. The research was conducted at Sun Rose Hydrofarm Greenhouse, Pancoran Mas, Depok City in March-April 2024. This study used a Randomized Complete Group Design (RCGD) with the treatment of the number of plants per planting hole consisting of five treatments as follows: 1 plant per planting hole, 2 plants per planting hole, 3 plants per planting hole, 4 plants per planting hole, and 5 plants per planting hole. The results showed that the treatment of 3 plants per planting hole was the optimal treatment and recommended for planting batik spinach with hydroponic floating raft system. The treatment of 3 plants per planting hole produces growth variables and production weight per plant that are not significantly different from the treatment of 1 plant per planting hole, and produces production weight per planting hole that is not significantly different from the treatment of 5 plants per planting hole.